La prestación del servicio postal universal en un contexto de precio uniforme y descremado del mercado: Existe riesgo de graveyard spiral? - Carlos Pateiro Rodríguez; Javier Prado Domínguez; Jesús M. García Iglesias (Atlantic Review of Economics, 2011)
– This paper focuses on the problems posed by the uniform price and market cream skimming in a context in which the incumbent is restricted asymmetric prices and products and analyzes the risks of a graveyard spiral process. We point that the price elasticity of demand, the brand loyalty and the adoption of policies promoting competition in the long term versus short-term approach can mitigate the financial problems of the universal service obligations (USO). Also, with the same objective we examined the role of a hypothetical relaxation of the universal postal service standards in the current context of rapid replacement of traditional mail by modern telecommunications.
Keywords: D42; L96; K20; K21; 330